Peramalan Curah Hujan Menggunakan Metode Holt-Winters Exponential Smoothing - Dzulfidho Wijianto Putra; Ahmad Fahrudi Setiawan; Nurlaily Vendyansyah (Journal of Information System Research (JOSH), 2026)
Rainfall is a crucial climatological parameter for agriculture, tourism, and water resource management. Its seasonal and fluctuating nature requires accurate forecasting methods to capture historical patterns. This study forecasts monthly rainfall using data from Ngaglik, Temas, and Tinjumoyo stations between January 2021 and December 2024, totaling 48 observations. The Holt–Winters Exponential Smoothing Additive method was chosen due to stable annual seasonal patterns. Model accuracy was assessed with Mean Absolute Error (MAE) and Root Mean Square Error (RMSE). Results show varying optimal parameters across stations. Ngaglik achieved the best performance with α = 0, β = 0, γ = 0.81, yielding MAE 64.39 mm and RMSE 90.84 mm. Temas recorded MAE 69.25 mm and RMSE 102.19 mm with γ = 0.78, while Tinjumoyo produced MAE 73.95 mm and RMSE 109.42 mm with γ = 0.56. This study highlights the effectiveness of Holt–Winters Additive forecasting and provides accuracy evaluations to support data-driven decisions in rainfall-dependent sectors.